A study on genus Chlamydatus Curtis, 1833 from China (Heteroptera: Miridae: Phylinae) - Li, Xiao-Ming; Liu, Guo-Qing (Zootaxa, 2006)
Five species of Chlamydatus Curtis from China are presented of which two, Chlamydatus laminatus and Chlamydatus sichuanensis, are described as new. A key for discrimination of the Chinese species is given. Photographs of the dorsal habitus, scanning electron micrographs of the metathorax scent-gland, and illustrations of the male genitalia and legs are provided. All type specimens are deposited in the Institute of Entomology, Nankai University, Tianjin, China.